Physicochemical and functional properties of spineless, short-spines, and long-spines sago starch - BUDI SANTOSO; Zita Letviany Sarungallo; ANGELA MYRRA PUSPITA (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Santoso B, Sarungallo ZL, Puspita AM. 2021. Physicochemical and functional properties of spineless, short-spines, and long-spines sago starch. Biodiversitas 22: 137-143. Starch application in the food and non-food industries is influenced by their properties. The aim of this research was to characterize the physicochemical and functional of spineless, short-spines, and long-spine sago starch. Starch morphology for all types had an oval shape with a smooth surface, which was proved by the X-ray diffraction analysis. The proximate composition did not differ for all types of sago, except the protein of spineless sago type was slightly higher but it did not affect the profile and gelatinization process. The amylose content of spineless, short spines and long spine of sago starch was 33.61 %db, 38.47 % db, and 37.59 % db, respectively; categorized as a high in amylose then tends to be stickyless. The value of peak viscosity and setback of spineless sago (7571.0 cP and 1495.0 cP) and long spines sago (7608.0 cP and 923.0 cP) were higher than the short spines sago starch (1271.0 cP and 538.0 cP). Therefore, the spineless and the long spines sago starch are suitable as thickener and fillers, while the short spines sago starch is suggested for cakes and bakery products because it will not harden when the product is cold.